SIMILARITIES AND DIFFERENCES OF DEGREE OF ADJECTIVE IN ENGLISH AND UZBEK LANGUAGES - Abdibayeva Nadya; Aziz Mukhamadiev (Лучшие интеллектуальные исследования, 2024)
Anotation: The study of adjective degrees is a topic of great scholarly interest since it provides insightful information about the comparative and superlative forms of adjectives, clarifying the complex expression of different degrees of attributes. The purpose of this article is to investigate the viewpoints of Uzbek and English academics regarding this linguistic issue. We attempt to examine and contrast the terminologies and approaches used in each language by exploring pertinent theories and using examples from Uzbek and English literature.